2009
DOI: 10.1002/jmri.21864
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of human skull in MRI using statistical shape information from CT data

Abstract: Purpose: To automatically segment the skull from the MRI data using a model-based three-dimensional segmentation scheme. Materials and Methods:This study exploited the statistical anatomy extracted from the CT data of a group of subjects by means of constructing an active shape model of the skull surfaces. To construct a reliable shape model, a novel approach was proposed to optimize the automatic landmarking on the coupled surfaces (i.e., the skull vault) by minimizing the description length that incorporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
2
8
1
Order By: Relevance
“…The proposed method is able to approximate the skull contours and differentiate air from bone with similar accuracy as the results presented in Wang et al (11), that reported a Dice coefficient of 0.75, even though they only showed results on the upper half of the skull. Additionally, their method requires previous annotation of the database by an expert, while our method requires no previous manual intervention.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The proposed method is able to approximate the skull contours and differentiate air from bone with similar accuracy as the results presented in Wang et al (11), that reported a Dice coefficient of 0.75, even though they only showed results on the upper half of the skull. Additionally, their method requires previous annotation of the database by an expert, while our method requires no previous manual intervention.…”
Section: Discussionsupporting
confidence: 74%
“…Rifai et al (10) proposed a three-dimensional (3D) method for segmenting bone regions in MRI volumes using deformable models and taking the partial volume effect into account. In Wang et al (11) the authors proposed the use of a CT database to create a reliable shape model used to locate the skull shape in MRI.…”
Section: Image Postprocessingmentioning
confidence: 99%
“…in facial sinuses in the head images [1]. To overcome this problem, several segmentation approaches have been proposed, such as a combination of consequent thresholding and mathematical morphological operations [8] or CT-derived model-based segmentation algorithms [9]. However, due to close signal intensity of cortical bone to that of air, these methods fail to robustly separate bony structures from proximal air cavities.…”
Section: Discussionmentioning
confidence: 99%
“…For scalp and skull segmentation from MRI, previous works in the literature have proposed the morphology method, machine‐learning‐based methods (Neural Network, SVM) and atlas‐based methods . Moreover, information from CT data can be used for segmentation.…”
Section: Introductionmentioning
confidence: 99%